The Relationship Between Digital Literacy in Disaster Management and Disaster Preparedness Among Students at STIKES RSPAD Gatot Soebroto - Riza Ginanjar Mustofa; Femi Kesumawati; Sofwan ㅤ (JOURNAL EDUCATIONAL OF NURSING(JEN), 2024)
Background: Indonesia is a country with a high level of disaster risk, making effective preparedness essential to mitigate the impact of disasters. In the digital age, disaster-related information can be obtained quickly through various digital platforms. The ability to access, understand, evaluate, and utilize disaster-related information is known as digital disaster literacy, which is believed to play a role in enhancing individual preparedness. Objective: To determine the relationship between digital disaster literacy and disaster preparedness among students at STIKES RSPAD Gatot Soebroto. Method: This study employed an analytical quantitative design with a cross-sectional approach. The study sample consisted of 120 students selected using proportional random sampling. Data were collected using questionnaires on digital disaster literacy and disaster preparedness. Data analysis was performed using the Chi-Square test with a 95% significance level. Results: The majority of respondents had “good” digital disaster literacy (65.0%) and were classified as “prepared” for disasters (60.0%). The analysis results showed that students with good digital disaster literacy were more likely to have good disaster preparedness (67.9%) compared to students with poor digital disaster literacy (45.2%). The Chi-Square test yielded a p-value of 0.020 (p < 0.05). Conclusion: There is a significant relationship between digital disaster literacy and disaster preparedness among students at STIKES RSPAD Gatot Soebroto.